Some Chemical and Physical Properties of Fruits of Different Mulberry Species Commonly Grown in Anatolia, Turkey - Gunes, Mehmet; Cekic, Cetin (Asian Journal of Chemistry, 2016)
Mulberry products known as pekmez, pestil and kome in Turkey have been widely consumed in Anatolia for a long time. Certain chemical and physical traits of mulberry affect the quality of these products. Soluble solid content (SSC), pH, titratable acid (TA), dry matter, must yield (unprocessed fruit juice) and fruit weight are some of the important characteristics of fruits to be processed. In this research, some physical and chemical characteristics of mulberry genotypes were determined. White (Morus alba), black (Morus nigra), red (Morus rubra) and pendulous (Momu alba var. pendula) mulberry genotypes were used in this study. The number of drupelets, percentage of parthenocarpy and number of full (not empty) seeds per fruit of species were also assessed. Bud burst, appearance of the inflorescence and harvesting dates were recorded as phenological traits. Smaller fruit size of pendulous mulberry, lower pH and higher acidity of black mulberry were the extreme characters when the species were compared.